ChemInform Abstract: Pentafulvene‐Derived η3‐Allyltitanocenes as Intermediates for the Stereoselective Functionalization of 5‐Membered Carbocycles. Issue 38 (30th August 2013) - Joseph, Jomy; Jaroschik, Florian; Radhakrishnan, K. V.; Vasse, Jean‐Luc; Szymoniak, Jan
Abstract Allyltitanocene complexes, generated by reacting pentafulvalenes with DIBAL‐H and TiCl2(Cp)2 react with aldehydes to afford homoallylic alcohols in a highly regio‐ and stereoselective manner.